Kinetic and Isotherm Studies of the Removal of Zn2+ Ions from Aqueous Solution by Modified Poly(ethylene terephthalate) Fibers - Azizinezhad, Fariborz (Asian Journal of Chemistry, 2013)
Modified poly(ethylene terephthalate) fibers were synthesized by the mixture of methyl methacrylate-acrylic acid in the presence of benzoyl peroxide as a radicalic initiator. The prepared copolymer was used as a new adsorbent for the removal of Zn2+ ions from aqueous solution. The isotherm and the kinetics data were fitted with (Langmuir, Freundlich, Temkin-Pyozhev) and (Lagergren pseudo-first-order, Ho's pseudo-second-order, intra-particle-diffusion) models, respectively. R2 values showed that the adsorption data were fitted by Freundlich isotherm and pseudo-second-order kinetics, as well. Thermodynamic parameters such as enthalpy (DHº), entropy (DSº) and Gibbs free energy (DGº) were determined, (0.0053 kJ/mol), (0.0085 kJ/mol K) and (-2.546, -2.675 and -2.803 kJ/mol), respectively. These results showed that the spontaneous and feasibility nature of the adsorption process. On the other hand, the overall activation energy (Ea) was calculated 1.895 kJ/mol.